Managing eWOM for hotel performance. Issue 3 (3rd July 2022) - Mathews, Shane; Prentice, Catherine; Tsou, Alice; Weeks, Clinton; Tam, Lisa; Luck, Edwina
ABSTRACT: Electronic word-of-mouth (eWOM) is an important marketing tool for achieving positive customer-related outcomes and firm performance. However, eWOM management is not well understood. This study explores how eWOM management can be utilized to optimize firm performance. Using a multiple case study approach, in-depth interviews were conducted with senior managers who were involved in the management of eWOM from nine hotels, and their websites and marketing materials were analyzed. eWoM digital platforms give even resource-constrained smaller hotels timely review analytics that can be used for the purpose of brand reputation strategy decisions. That is, those hotels that focus their limited resources on developing authentic response systems and create unique communication capabilities which are leveraged for eWOM reputation as a competitive advantage. These findings highlight that successful hotels use eWoM data analytics for decisions related long-term signaling strategies: as hotels can extend their authentic voice or an organizational character within their eWOM responses over time to complement their optimal brand position.